2016
DOI: 10.14336/ad.2015.1030
|View full text |Cite
|
Sign up to set email alerts
|

Higher Plasma LDL-Cholesterol is Associated with Preserved Executive and Fine Motor Functions in Parkinson’s Disease

Abstract: Plasma low density lipoprotein (LDL) cholesterol has been associated both with risk of Parkinson’s disease (PD) and with age-related changes in cognitive function. This prospective study examined the relationship between baseline plasma LDL-cholesterol and cognitive changes in PD and matched Controls. Fasting plasma LDL-cholesterol levels were obtained at baseline from 64 non-demented PD subjects (62.7 ± 7.9 y) and 64 Controls (61.3 ± 6.8 y). Subjects underwent comprehensive neuropsychological testing at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 46 publications
7
39
2
Order By: Relevance
“…These findings were similar for non‐HDL‐C levels and across all applied sensitivity analyses. Our results are in line with other studies that have also found an inverse association of hypercholesteremia, TC, and LDL‐C with PD risk, with earlier PD onset, and with modestly slower progression of PD symptoms and improved fine motor speed skill over time …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings were similar for non‐HDL‐C levels and across all applied sensitivity analyses. Our results are in line with other studies that have also found an inverse association of hypercholesteremia, TC, and LDL‐C with PD risk, with earlier PD onset, and with modestly slower progression of PD symptoms and improved fine motor speed skill over time …”
Section: Discussionsupporting
confidence: 93%
“…First, although the exclusion of statin users enabled us to carefully evaluate cholesterol‐PD risk, it also excluded individuals with the highest cholesterol levels. However, 30% of the entire statin‐free cohort had borderline high LDL‐C (≥140 mg/dL) and TC (≥210 mg/dL) levels similar to the other studies that included individuals who were statin and nonstain users . In addition, it is possible to characterize these individuals with a tendency to avoid or delay pharmacotherapy in general and who choose other methods to treat chronic conditions.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Despite the literature linking serum/plasma total and LDL cholesterol to PD, the cause of the association is not known and further complicated by the compartmentalization of the brain and peripheral cholesterol. An investigation of a potential causal relationship between circulating cholesterol levels and PD took into consideration age, gender, APOE polymorphisms, smoking history, statin, and several related gene single nucleotide polymorphisms.…”
Section: Contributions From the Basic Sciencesmentioning
confidence: 99%